Synthesis and characterisation of the ethylene bridged permethylindenyl cerium complex [(EBI*)CeI(THF)]. - Ransom, P; Arnold, T; Thompson, A; Buffet, J; O'Hare, D (2012)
Synthesis, magnetic properties, NMR spectroscopy, and crystallographic details of an ethylene bridged hexamethylindenyl (EBI*) cerium iodide complex [(EBI*)CeI(THF)] are reported.